SELECTING SURROUND PULSED LASER HARDENING (VPLH) FOR WEAR OF CUTTING TOOLS - Igor Aleksandrovich Pinahin; Stanislav Aleksandrovich Toeskin (Вестник Северо-Кавказского федерального университета, 2022)
Results of influence studies of rising by the method of volume pulsed laser processing hard alloys cutting instruments on them wear.